Implementation of the Basics and Stages of Democracy Based on Pancasila as a Form of Community Service in the Election of Student Council Chair at SMPN 41 Medan - Siregar, Anna Sari Ashabul Jannah; Girsang, Aulia Anggraini; Lestari, Bunga Indah; Situmorang, Desy Natalye Br; Siregar, Novita Angelin; Gultom, Paskah Monika Putri (Holistic Science, 2024)
This paper discusses the importance of democracy education based on Pancasila in the context of the election of the Student Council Chairman at SMPN 41 MEDAN. Strong democracy education plays a key role in shaping students' character and leadership, as well as facilitating active participation in school life. Through understanding and implementing the values of democracy, students can be equipped with the skills and attitudes needed to become responsible and integrity-driven citizens. The research method used is qualitative research. One type of qualitative research used is ethnographic research to understand the dynamics of democracy in the school environment. The results show that understanding democracy, educating about examples of democracy in everyday life, and providing an understanding of citizenship rights are important steps in strengthening democratic values among students